(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Now days, manufacturing sectors replaced most expensive and casted components by means of sheet metal parts. From this phenomenon the cost of the products and the weight of the components are reduced as much as possible. The cost of tooling in sheet metal industries contributes a considerable part to the overall cost of manufacturing a component. It is therefore imperative to keep down this cost by ensuring that the tool works for a long period in production without interruption. In this project a Piercing Die is design and develop which consist of number of parts like housing, punch, punch holder, striper, cutting die, top plate, bottom plate etc. for piercing a 12 hole work piece, by considering various important parameters of die such as Causes of bur, causes of failure of punch, cost effect of failure, tool life, productivity etc. These problems bring the piercing die to improve tool life, increasing productivity, without increase in trial cost in design.